Swelling prediction of AISI 304 and 18Cr10NiTi austenitic stainless steels using various empirical functions - Kalchenko, A.S.; Lazarev, N.P. (Вопросы атомной науки и техники, 2022)
A review of the known empirical dependences of austenitic steel swelling on in-reactor environments is carried out. The performance of empirical functions is compared in application to the conditions of thermal neutron reactor internals. Comparison with experimental data is made, and the influence of statistical errors of reactor data is discussed. Finally, the applicability of the empirical functions in the space of external parameters, precisely temperature, dose, and dose rate, is investigated.